Macronutrient intake and nutritional status related to length of stay in Tugu Ibu Hospital - Nenny Fatimah; Adhila Fayasari (Sarana Ilmu Indonesia (salnesia), 2024)
The incidence of malnutrition in the hospital is largely undetectable and considered important to measure the length of stay. Nutrient intake and assessment of nutritional status from the outset of patients treated for factors that affect the morbidity and mortality rate, length of hospitalization, and maintenance costs. energy intake and carbohydrate intake with length of stay (p 0,030 OR 2,3; p 0,046 OR 2,76) and there was a significant relationship between nutritional status and length of stay (p 0,024). There was a relationship of energy intake, carbohydrate intake and nutritional status with the length of stay.